Sikap Hukum Islam Terhadap Tindakan Terorisme - Rohidin Rohidin (Jurnal Hukum IUS QUIA IUSTUM, 2003)
Islam is vefy untolerable the violence in any form and any purpose. Although, Islam in certain condition, the apply of violence is permissible but it must be taken on the law corridor. It means that the violence could be applied along with meeting the requirements,like the law sanction of violence, where such law sanction appear of expressing on anti violence in Islam.